The Effect of Sexual Ethics Education on Adolescents at SMP Negeri 1 Pematang Bandar - Esti Marlina Sirait; Esther Sitorus (research, training and philanthropy institution Natural Aceh, 2023)
This study aimed to determine the effect of sexual ethics education on adolescents at Pematang Bandar Middle School for the 2020/2021 academic year. The sample in this study was all 40 grade VIII students of SMP Negeri 1 Pematang Bandar. The technique used to analyze research data is quantitative data analysis. The data obtained in quantitative form is converted into qualitative data concerning the Likert scale. Data were analyzed using descriptive and inferential statistical techniques. From the study results, it can be concluded that there is a significant influence on sexual ethics education on the treatment of adolescents at SMP Negeri 1 Pematang Bandar for the 2020/2021 academic year. The conclusions from the research were given to every teacher there to pay more attention to every act of behavior shown by each student in their development into adulthood.